Toward an Analytical Framework for the Study of Race and Police Violence. (March 2017) - Rivera, Mario A.; Ward, James D.
Abstract: Treatments of race and police violence in the fields of public administration and policy have drawn eclectically from many disciplinary sources in historical, political, and managerial analysis. From an institutional perspective, emphasis has been on how organizational practices, rules, norms, and values, along with role socialization, shape germane behavior. Of particular interest to the authors is the phenomenon of race‐related police violence in its systemic but also attitudinal and behavioral manifestations in the policing role. How does an academic or practitioner researcher specify evaluative perspectives applicable to this policy and administrative challenge? There is a prior need for defined analytical and ethical positions drawing closely from public administration and policy sources. This article suggests ways to develop such grounded frameworks, built on these distinctive traditions but also going beyond them, so as to allow for an integrative approach to evaluative analysis and action on this grave and contentious issue . Abstract : Related Content:Ward and Menifield (PAR March/April 2017) Related Content:Robinson and Ramsey (PAR March/April 2017) Related Content:Pegues (PAR March/April 2017) Related Content:Ward (PAR March/April 2017) Related Content:Epp, Maynard-Moody, and Haider-Markel (PAR March/April 2017) Related Content:Davenport (PAR March/April 2017) Related Content:Eterno, Barrow, and Silverman (PAR March/April 2017) Related Content:DeBenedetto (PAR March/April 2017) Related Content:Hong (PAR March/April 2017) Related Content:Nicholson-Crotty, Nicholson-Crotty, and Fernandez (PAR March/April 2017) Related Content:Jennings and Rubado (PAR March/April 2017) Related Content:Fretwell and Lombardo (PAR March/April 2017) Related Content:Ho and Cho (PAR March/April 2017) Related Content:Villegas (PAR March/April 2017) Related Content:Menifield (PAR March/April 2017) Related Content:Mead (PAR March/April 2017) Related Content:Middlemass (PAR March/April 2017) Related Content:Rollins and Hilliard (PAR March/April 2017)